2019
DOI: 10.1001/jamasurg.2019.2985
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Surgery Residents About Parental Leave During Training

Abstract: IMPORTANCE To our knowledge, there has been little research conducted on the attitudes of residents toward their pregnant peers and parental leave. OBJECTIVE To examine the perceptions of current surgery residents regarding parental leave. DESIGN, SETTING, AND PARTICIPANTS A 36-item survey was distributed to current US general surgery residents and residents in surgical subspecialties through the Association of Program Directors in Surgery listserv and social media platforms. Questions were associated with gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 18 publications
6
81
0
Order By: Relevance
“…It additionally reported that those who had graduated from medical school more recently were more likely to have a pregnancy during training than their older counterparts. The finding that childrearing does not affect attrition or performance should encourage residency programmes to develop clear guidance regarding parental leave, as in a recent study only 3.8% of residents were able to correctly identify the American Board of Surgery policy and felt unsupported [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It additionally reported that those who had graduated from medical school more recently were more likely to have a pregnancy during training than their older counterparts. The finding that childrearing does not affect attrition or performance should encourage residency programmes to develop clear guidance regarding parental leave, as in a recent study only 3.8% of residents were able to correctly identify the American Board of Surgery policy and felt unsupported [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Trainees often report a perception of stigma and a lack of support for prospective and new parents, both by other trainees and by faculty. 18,19 Larger studies of parental leave policies across multiple specialties and institutions have similarly described a lack of standardized/formal GME parental leave policy across specialties and lack of specific references about the impact of parental leave on clinical training (length and eligibility for specialty boards). 6,[20][21][22] While it has been established that parenthood during GME is an important component of trainee well-being, 23 specific barriers to implementation of standardized policies that have been identified include: stigma, financial concerns, workforce and duty hour challenges, as well as the rigidly specified timeline of progression from one stage of medical training to the next.…”
Section: Discussionmentioning
confidence: 99%
“… 14 17 Trainees often report a perception of stigma and a lack of support for prospective and new parents, both by other trainees and by faculty. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…Infertility is seemingly more prevalent in physicians than in the general population, at least among females 4 . This condition is also worsened by several factors, such as excessive stress, frequent night shifts and, in many cases, lacking support from peers and faculty or the need to delay pregnancy or fatherhood in order to achieve economic stability 5 …”
mentioning
confidence: 99%
“…4 This condition is also worsened by several factors, such as excessive stress, frequent night shifts and, in many cases, lacking support from peers and faculty or the need to delay pregnancy or fatherhood in order to achieve economic stability. 5 My story with infertility begins a few years ago. At the time I had already been "working" as an andrologist for almost 8 years, between med school, training and residency; my wife, two years younger than me, was at the time a resident in paediatrics.…”
mentioning
confidence: 99%